Early Complications of Hyperleukocytosis and Leukapheresis in Childhood Acute Leukemias. Issue 2 (March 2016) - Abla, Oussama; Angelini, Paola; Di Giuseppe, Giancarlo; Kanani, Mohamed F.; Lau, Wendy; Hitzler, Johann; Sung, Lillian; Naqvi, Ahmed
Abstract : Hyperleukocytosis in children with acute lymphoblastic leukemia (ALL) and acute myeloid leukemia (AML) is associated with early morbidity and mortality. The benefit from leukapheresis is controversial, and its complications are not well defined. We analyzed the frequency of early complications in children with ALL and AML presenting with white blood cell (WBC) count >100×10 9 /L, and the type and frequency of complications related to leukapheresis. During a 12-year period, 84 of 634 (13%) ALL and 18 of 143 (12.5%) AML patients presented with hyperleukocytosis. Leukapheresis was performed in 18 ALL and 12 AML patients. The median initial WBC was 474×10 9 /L in the leukapheresis group compared with 175×10 9 /L in the nonleukapheresis group. Neurological leukostasis occurred in 6 ALL (7.1%) and 4 AML (22.2%) patients. Pulmonary leukostasis occurred in 16 ALL (19%) and 4 AML patients (22.2%). Neurological symptoms improved in few patients after leukapheresis, except in patients with very high WBC (>650×10 9 /L in ALL and >400×10 9 /L in AML). Leukapheresis improved respiratory symptoms in some patients but caused worsening symptoms in others. Early death was associated with neurological complications, AML diagnosis, and coagulopathy. Leukapheresis did not delay initiation of chemotherapy, nor did it impact early response to chemotherapy or long-term survival. Complications included femoral vein thrombosis, electrolyte imbalances, and hemodynamic instability, which were all reversible. The role of leukapheresis as a cytoreductive procedure in childhood hyperleukocytic leukemia remains to be well defined.